Correlation Between Social Support and Anxiety in Facing Learning Evaluations Among First-Year Health Science Students - Hidayat, Faried Rahman; Azizah, Regina Nur (Inspirasi Foundation, 2025)
Background : Anxiety is a psychological condition of an individual that arises because there is a trigger that is characterized by feelings of fear, tension, worry, restlessness accompanied by physical responses such as a pounding heart, high blood pressure and so on depending on what each individual feels. Anxiety is common in students, especially in the academic sphere, one way that can reduce anxiety is Social Support (Parents and Peers). Social Support is a form of support given to individuals who are experiencing difficulties to reduce the feelings of anxiety that are being felt. Objective : To determine the relationship between social support (parents and peers) and anxiety of first semester students in facing learning evaluation in the UMKT Nursing Undergraduate Study Program. Method : This study used the Hamilton Rating Scale For Anxiety (HARS) measuring instrument with a Likert scale, and the Social Support (Parents and Peers) measuring instrument adapted through the Sarafino (2012) questionnaire Guttman scale with a reliability value of 0.635. The design of this study was a Cross Sectional study. The sample of this study was determined by the Slovin formula, obtaining a sample of 108 respondents. Data were obtained using a questionnaire. This study used univariate data analysis and bivariate analysis. The Chi-square test was used to determine the correlation between two variables. Results : Based on the results of the Chisquare statistical test, the results obtained (p value = 0.025 p value = <(0.05) so that it can be said that H0 is rejected and Ha is accepted which states that there is a significant relationship, which means that the greater the social support received, the more it will affect the anxiety felt. It is recommended for further research to conduct Multiple regression research so that it can examine more than two variables simultaneously, such as examining other factors that influence social support with student anxiety such as physical needs, social needs and psychological needs. As well as the Spearman Rank statistical test to see the results of meaningful correlations and the strength of the correlation. Conclusion : There is a Relationship Between Social Support (Parents and Peers) and Anxiety of Semester 1 Students in Facing Learning Evaluation in the UMKT Nursing Undergraduate Study Program